2022
DOI: 10.1002/ptr.7354
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones protects against cognitive deficits induced by chronic sleep deprivation via alleviating oxidative stress and suppressing neuroinflammation

Abstract: Mounting evidence suggests that there is a close association between chronic sleep deprivation (CSD) and cognitive deficits. The animal model of CSD‐induced cognitive deficits is commonly used to seek potential treatments. Soy isoflavones (SI) have been reported to possess antioxidant, anti‐inflammation, and neuroprotective effects. In the present study, the effects of SI on CSD‐induced memory impairment were investigated. The mice were subjected to the sleep interruption apparatus and continuously sleep depri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The levels of pro‐inflammatory cytokines were found to be increased in the peripheral blood of patients with sleep disorders (Irwin et al., 2016 ; Xia et al., 2021 ). In addition, sleep deprivation significantly elevated the levels of proinflammatory cytokines including IL‐1β, IL‐6, and TNF‐α in the hippocampus and resulted in cognitive impairment during the novel object recognition test (Lu et al., 2022 ). In line with these previous studies, the results showed that the levels of IL‐1β, IL‐6, and TNF‐α were increased in the hippocampus of the mice exposed to CSD, which contributed to the observed cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of pro‐inflammatory cytokines were found to be increased in the peripheral blood of patients with sleep disorders (Irwin et al., 2016 ; Xia et al., 2021 ). In addition, sleep deprivation significantly elevated the levels of proinflammatory cytokines including IL‐1β, IL‐6, and TNF‐α in the hippocampus and resulted in cognitive impairment during the novel object recognition test (Lu et al., 2022 ). In line with these previous studies, the results showed that the levels of IL‐1β, IL‐6, and TNF‐α were increased in the hippocampus of the mice exposed to CSD, which contributed to the observed cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic SD promotes the transformation of microglia into the neurotoxic M1 phenotype and subsequently induces the NF-κB pathway to increase the release of pro-inflammatory factors (TNF-α, IL-6), causing neuroinflammatory response, aggravating hippocampal neuron damage, and affecting cognitive function [ 55 ]. Further studies found that SD increased the protein levels of the pro-inflammatory cytokines TNF-α, IL1-β, IL-6, and IL-8 but decreased the protein levels of the anti-inflammatory cytokines IL-4 and IL-10 in the rat hippocampus [ 55 , 57 , 102 , 103 , 104 ]. Serum levels of pro-inflammatory cytokines (IL-6, IL-1β, TNF-α) increased in SD rats after 24 h of SD, and the effect was more significant in cerebrospinal fluid after 72 h of SD (IL-1β: 30.2 ± 12.8 pg·mL −1 →43.6.8 ± 9.4 pg·mL −1 ; IL-6: 28.8 ± 9.3 pg·mL −1 →37.8 ± 7.4 pg·mL −1 ; TNF-α:19.1 ± 6.3 pg·mL −1 →21.8 ± 7.4 pg·mL −1 ).…”
Section: Potentially Relevant Mechanismsmentioning
confidence: 99%
“…9 A recent study showed that SI offer good therapeutic and/or preventive potential for Parkinson's disease (PD), which is associated with dysregulated mitophagy. 10 Our previous studies had found that SI can protect against cognitive deficits induced by chronic sleep deprivation by alleviating oxidative stress and suppressing neuroinflammation, 11 as well as reverse chronic ethanol exposure-induced cognitive dysfunction by enhancing synaptic plasticity and inhibiting neuronapoptosis. 12 Depression evokes the activation of microglia and promotes the production of proinflammatory cytokines (TNF-α, IL-6 and IL-1β) in the cortex and hippocampus of mice.…”
Section: Introductionmentioning
confidence: 99%